2022
DOI: 10.1177/13623613221086700
|View full text |Cite
|
Sign up to set email alerts
|

Does learning you are autistic at a younger age lead to better adult outcomes? A participatory exploration of the perspectives of autistic university students

Abstract: Many autistic people do not learn they are autistic until adulthood. Parents may wait to tell a child they are autistic until they feel the child is “ready.” In this study, a participatory team of autistic and non-autistic researchers examined whether learning one is autistic at a younger age is associated with heightened well-being and Autism-Specific Quality of Life among autistic university students. Autistic students ( n = 78) completed an online survey. They shared when and how they learned they were auti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 72 publications
2
42
0
Order By: Relevance
“…Previous qualitative findings have indicated that autistic YP often distance themselves from the autism label (Calzada, Pistrang, & Mandy, 2012 ; MacLeod, Lewis, & Robertson, 2013 ). Recent quantitative research demonstrated that length of time since autism diagnosis was associated with more positive well‐being: it is possible that over time, autism diagnoses are assimilated into one's sense of self‐leading to more positive outcomes (Oredipe et al., 2022 ), and the qualitative findings in this study support this hypothesis. Parents and YP clinicians often placed more emphasis on autism as an important part of their child's identity than the YP themselves.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Previous qualitative findings have indicated that autistic YP often distance themselves from the autism label (Calzada, Pistrang, & Mandy, 2012 ; MacLeod, Lewis, & Robertson, 2013 ). Recent quantitative research demonstrated that length of time since autism diagnosis was associated with more positive well‐being: it is possible that over time, autism diagnoses are assimilated into one's sense of self‐leading to more positive outcomes (Oredipe et al., 2022 ), and the qualitative findings in this study support this hypothesis. Parents and YP clinicians often placed more emphasis on autism as an important part of their child's identity than the YP themselves.…”
Section: Discussionsupporting
confidence: 72%
“…Furthermore, it was not possible to record characteristics of potentially eligible participants who declined to share their details with the research team: possible factors for declining to participate could be having less positive rapport with healthcare clinicians, less investment in one's autism diagnosis, more severe mental health needs or in the case of YP, having parents who are unsupportive regarding their gender identity: such individuals may therefore be underrepresented in our sample. Half the autistic adults were diagnosed with autism in adulthood and therefore may well have had different perspectives on autism (Oredipe et al., 2022 ). However, a strength of IPA analysis is that context and idiography directly inform the analysis, so these different perspectives and life experiences are considered throughout the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Ritsher et al suggest that although one’s individual history of discrimination may affect their morale and view of their disability, the impact of stigma on well-being is malleable. It might also be that for those who receive their diagnosis later in life, the diagnosis can represent a sense of relief or sense-making about their experience (Harmens et al, 2022; Oredipe et al, 2022) or include sources of information that are more neurodiversity-affirming (e.g. social media; Bury et al, 2022), and thus be more positively associated with their own identity.…”
Section: Discussionmentioning
confidence: 99%
“…Most used at least one informational resource to help their child understand the diagnosis (Kiely et al, 2020). Oredipe et al (2022) asked autistic university students when and how they would "tell their own autistic child about autism?" The participants offered several recommendations, such as considering the child's developmental level, curiosity, and personality, but all emphasized the importance of early disclosure.…”
Section: Talking With Children About Autismmentioning
confidence: 99%
“…Riccio et al (2020) found that autistic adolescents who had been voluntarily informed of their diagnosis by their parents tended to incorporate their unique strengths into their personal de nitions of autism, compared to adolescents whose parents had not told them about the diagnosis, or had told them involuntarily. Oredipe et al (2022) examined the effects of autism disclosure on well-being and quality of life (QoL) in a sample of autistic university students, and found disclosure at a younger age was associated with higher well-being and QoL. In contrast, Leung et al (2023) examined a more sociodemographically diverse sample of autistic adults, and found that age of disclosure did not predict QoL and well-being in adulthood.…”
Section: Introductionmentioning
confidence: 99%